Malaria Communication Strategy for Malawi Policy - Malawi Government: Ministry of Health (Malawi Government, 2021)
Malaria is a major public health problem in Malawi. It is the leading cause of morbidity and mortality in children under five years of age and pregnant women. It is the most common cause of outpatient visits, hospitalization and death. Malaria is also a developmental problem as it has a serious socioeconomic impact on families and the nation, through loss of work, school absenteeism and high levels of expenditures on treatment. The government of Malawi through the Ministry of Health and its partners are committed to controlling malaria in the country. As part of malaria control strategies, the Ministry has developed several guiding malaria documents one of which is the Malaria Communication Strategy for Malawi for 2009 to 2015. Using the strategy as a guide, behaviour change communication will lead to improved community uptake of malaria control interventions. The main malaria behaviours that need to be adopted and maintained by individuals, families and communities, include, among others, Malaria Case Management, Intermittent Preventive Treatment (IPT) of pregnant women with SP and malaria prevention with special emphasis on Insecticide Treated Nets/ Long Lasting Insecticide Treated Nets (ITNs / LLINs) and Indoor Residual Spraying (IRS). I am hopeful that concerted efforts to implement this malaria communication strategy with support of global, regional and national partners will enable Malawi to significantly reduce the health and socioeconomic burden of malaria.